Imagining the world from behind the Iron Curtain youth and the global sixties in Poland - Fidelis, Malgorzata 1971- (Oxford scholarship online, 2022)
The sixties occupy a prominent place in popular culture and scholarship as an era of global upheavals, including the Civil Rights Movement, de-colonization, radical social movements, student and youth protests, and the Vietnam War. This pioneering book explores the seemingly isolated Eastern bloc and a non-capitalist context, demonstrating the impact of those global upheavals on young people in Poland in the form of international youth culture, protest movements, and counterculture